A modified particle swarm optimization procedure for triggering fuzzy flip-flop neural networks - Kowalski, Piotr A.; Słoczyński, Tomasz (Zielona Góra: Uniwersytet Zielonogórski)
The aim of the presented study is to investigate the application of an optimization algorithm based on swarm intelligence to the configuration of a fuzzy flip-flop neural network. Research on solving this problem consists of the following stages. The first one is to analyze the impact of the basic internal parameters of the neural network and the particle swarm optimization (PSO) algorithm.
Keywords: fuzzy neural network; fuzzy flip-flop neuron; particle swarm optimization; training procedure; regression